Divergent developmental trajectories in two siblings with neuropathic mucopolysaccharidosis type II (Hunter syndrome) receiving conventional and novel enzyme replacement therapies: A case report - Kazuyoshi Tomita; Shungo Okamoto; Toshiyuki Seto; Takashi Hamazaki; Sairei So; Tatsuyoshi Yamamoto; Kazunori Tanizawa; Hiroyuki Sonoda; Yuji Sato (JIMD Reports, 2021)
Abstract Mucopolysaccharidosis type II (MPS II; Hunter syndrome) is an X‐linked recessive lysosomal storage disease caused by a mutation in the IDS gene and characterized by systemic accumulations of glycosaminoglycans. Its somatic symptoms can be relieved by enzyme replacement therapy (ERT) with idursulfase, but because the enzyme cannot cross the blood‐brain‐barrier (BBB), it does not address the progressive neurodegeneration and subsequent central nervous system (CNS) manifestations seen in patients with neuropathic MPS‐II. However, pabinafusp alfa, a human iduronate‐2‐sulfatase (IDS) fused with a BBB‐crossing anti‐transferrin receptor antibody, has been shown to be efficacious against both the somatic and CNS symptoms of MPS II. We report two cases of MPS‐II in Japanese siblings sharing the same G140V mutation in the IDS gene, who showed markedly contrasting developmental trajectories following enzyme replacement therapy (ERT). Sibling 1 was diagnosed at 2 years of age, started undergoing conventional ERT shortly afterward, and scored a developmental quotient (DQ) of 53 on the Kyoto Scale of Psychological Development (KSPD) at 4 years of age. Sibling 2 was diagnosed prenatally and received conventional ERT from the age of 1 month through 1 year and 11 months, when he switched to pabinafusp alpha. He attained a DQ of 104 at age 3 years and 11 months, along with significant declines in heparan sulfate concentrations in the cerebrospinal fluid. This marked difference in neurocognitive development highlights the importance of early initiation of ERT with a BBB‐penetrating enzyme in patients with neuropathic MPS‐II.